Zyklophin, a short-acting kappa opioid antagonist, induces scratching in mice - DiMattio, K.M. (2014)
It has been shown previously that norbinaltorphimine (norBNI) and 5΄-guanidinonaltrindole (5΄-GNTI), long-acting kappa opioid receptor (KOPR) antagonists, cause frenzied scratching in mice [1;2]. In the current study, we examined if zyklophin, a short-acting cyclic peptide KOPR antagonist, also elicited scratching behavior. When injected s.c. in the nape of the neck of male Swiss-Webster mice, zyklophin at doses of 0.1, 0.3 and 1 mg/kg induced dose-related hindleg scratching of the neck between 3 and 15 min after injection. Pretreating mice with norBNI (20 mg/kg, i.p.) at 18–20 hr before challenge with zyklophin (0.3 mg/kg) did not markedly affect scratching. Additionally, KOPR −/− mice given 0.3 mg/kg of zyklophin displayed similar levels of scratching as wild-type animals. The absence of KOPR in KOPR −/− mice was confirmed with ex vivo radioligand binding using [(3)H]U69,593. Taken together, our data suggest that the presence of kappa receptors is not required for the excessive scratching caused by zyklophin. Thus, zyklophin, similar to the structurally different KOPR antagonist 5΄-GNTI, appears to act at other targets to elicit scratching and potentially the sensation of itch.